Analysing discrete event simulation modelling activities applied in manufacturing system design - Johansson, J. (Cranfield University Press, 2009)
In manufacturing industry, Discrete Event Simulation (DES) is applied in just a small fraction of the cases where it could give significant value. The complexity of the DES technology itself is one barrier to achieving its full potential in manufacturing system design. This paper focuses on methodologies which can be used in studying the modelling process, with the specific intent of integrating DES into the engineering design process of manufacturing systems. Ethnographical methodologies are proposed, as they are successfully applied to the analysis of the engineering design process. Observations from industrial practice indicate that visualisation in DES software is essential for the sequential verification of design activities.
Organised by: Cranfield University
Keywords: Discrete Event Simulation; Manufacturing system design; Engineering design